PENGARUH IMPLEMENTASI MANAJEMEN KUALITAS TERHADAP KINERJA KARYAWAN DENGAN MEDIASI KEPUASAN KERJA (STUDY PADA CV. RYUR NAMURI CHAN DI DESA KUBANG KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA) - Kelvin, Kelvin; Samsir, Samsir; Rio, Marpaung Jones (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to find out how the influence of Quality Management Implementation (X) on Employee’s Performance (Y) by mediating Job Satisfaction (M) at CV. Ryur Namuri Chan In Kubang Village, Guguak District, Lima Puluh Kota Regency. The population in this study included all employees at CV. Ryur Namuri Chan, which amounts 63 people.Primary data were collected using a questionnaire as an instrument for research results, to test the hypothesis in this study was to use SEM-PLS with the help of the SmartPLS program. The sampling technique chosen was the census method (63 employees at CV. Ryur Namuri Chan in Kubang Village, Guguak District, Lima Puluh Kota Regency). The results showed that: 1) There is a positive and significant influence on the implementation of quality management on job satisfaction at CV. Ryur Namuri Chan, 2) There is a positive and significant influence on the implementation of quality management on employee’s performance, 3) There is a positive and significant effect of job satisfaction on employee performance, 4) The mediation test show that job satisfaction provides a mediating role in the implementation of quality management on Employee Performance at CV. Ryur Namuri Chan.Keyword: Quality Management Implementation, Employee’s Performance, Job Satisfaction.